Natural Rubber Latex (NRL) and Rice Starch as an Alternative Binder in Wood Composite Industry - Jayshree, Thraisingam; Gupta, Arun; Malini, Subramaniam (AENSI Publishing, 2016)
Medium density fiberboards (MDF) was produced in laboratory using bio-adhesives synthesized using natural rubber latex (NRL) and rice starch (RS) with pressing time of 3 minutes, temperature of 180°C and pressure of 5MPa. This present study is aimed on increasing and improving the physical and mechanical performances of MDF by application of bio-based adhesives which comprises NRL and rice starch solution. The effects of bio-adhesives used on the physical and mechanical properties of boards produced were investigated accordingly and compared with the MDF prepared using urea-formaldehyde according to the specific ASTM standards. In the composite preparation, bio- adhesives were used as manipulated variable, where they were split into 5 further weight proportions as follows: 1) 20g NRL; 2) 15g NRL + 5g RS; 3) 10g NRL + 10g RS; 4) 5g NRL + 15g RS and 5) 20g RS. The samples were also subjected to mechanical testing such as modulus of rupture (MOR), internal bonding (IB) and thickness swelling (TS). Based on the mechanical testing done on the specimens, it is clearly indicated that bioadhesives comprising of 15g of natural rubber latex and 5 g of rice starch blend improves the modulus of rupture (MOR) and internal bonding strength (IB) of MDF significantly, where the mechanical strength value obtained were better and comparable than MDF made with UF alone. Hence, it strongly indicates the promising feasibility of NRL and rice starch to replace conventional UF in wood composite industry, and eventually highlights the success of this research.